Does simian virus 40 DNA integrate into cellular DNA during productive infection? - Rigby, P W (1978)
Late after infection of permissive monkey cells by simian virus 40 (SV40), large amounts of SV40 DNA (30,000 to 220,000 viral genome equivalents per cell) can be isolated with the high-molecular-weight fraction of cellular DNA. Hirai and Defendi (J. Virol.9:705-707, 1972) and Hölzel and Sokol (J. Mol. Biol. 84:423-444, 1974) suggested that this SV40 DNA is covalently integrated into the cellular DNA. However, our data indicate that the high-molecular-weight viral DNA is composed of tandem, "head-to-tail" repeats of SV40 DNA and that very little, if any, of this viral DNA is covalently joined to the cellular DNA. This was deduced from the following experimental findings. The size of the SV40 DNA associated with the high-molecular-weight cellular DNA fraction is greater than 45 kilobases, based on its electrophoretic mobility in agarose gels. In this form the SV40 DNA did not produce heteroduplex structures with a marker viral DNA (an SV40 genome with a characteristic deletion and duplication). After the high-molecular-weight DNA was digested with EcoRI or HpaII endonucleases, enzymes which cleave SV40 DNA once, more than 95% of the SV40 DNA migrated as unit-length linear molecules and, after hybridization with the marker viral DNA, the expected heteroduplex structures were easily detected. Digestion of the high-molecular-weight DNA fraction with restriction endonucleases that cleave cellular, but not SV40. DNA did not alter the electrophoretic mobility of the polymeric SV40 DNA, nor did it give rise to molecules that form heteroduplex structures with the marker viral DNA. Polymeric SV40 DNA molecules produced after coinfection by two physically distinguishable SV40 genomes contain only a single type of genome, suggesting that they arise by replication rather than by recombination. The polymeric form of SV40 DNA is highly infectious for CV-1P monolayers (6.5 X 10(4) PFU per microgram of SV40 DNA), yielding virtually exclusively normal, covalently closed circular, monomer-length DNA. Quite clearly these cells have an efficient mechanism for generating monomeric viral DNA from the SV40 DNA polymers.